An Issue Passed on To The Republic: Bektashism (1921-1931) (Journal of Alevism-Bektashism Studies, 2025)
The issue of Bektashism, inherited by the Republic, is a continuation of the religion-science or progressivism-reactionarism debate seen during the Second Constitutional Era. During the years of the Second Constitutional Era, Westerners suggested reforms in the Empire, they argued that religious affairs should also be reformed in the age of science, Kılıçzade Hakkı, among the Westerners, stated that lodges and zawiyas should be closed. During the years of the National Struggle, under the leadership of Mustafa Kemal, the debate which was interrupted due to the will to bring together all the elements in a broad front policy, resurfaced with the novel Nur Baba by Yakup Kadri (Karaosmanoğlu) before the republic was declared. After Nur Baba, Besim Atalay’s book Bektaşilik ve Edebiyatı in 1924, a series of articles on Bektashism in the Büyük Gazete in 1926, Baha Said’s articles on Alevism in the Türk Yurdu in the same year, the story Bir Genç Kız Bektaşiler Arasında written by Peyami Safa under the name Server Bedi in 1927, and Yusuf Ziya (Yörükan)’s field study was published in 1928. In the same year, F. R. Haslok’s translation of Bektaşi Tedkikleri, Ziya Bey’s article series published in Yeni Gün newspaper in 1931, and J. K. Birge’s research titled Bektaşilik Tarihi, which refers to Ziya Bey in 1931, was published in 1937. In the early Republican years, studies researched Bektashism from its geography to its literature, literary publications and newspaper articles mentioned here directly or indirectly defended the closure of the Bektashi sect, and became the elements of a campaign for the complete liquidation of Bektashism after the sect was closed. Besim Atalay, Baha Said, Yusuf Ziya (Yörükan) tried to find a place for Bektashism in the regime in the context of Turkish culture, while people such as Yakup Kadri, Peyami Safa and Ziya Bey claimed the harms of Bektashism and stated directly or indirectly that it should be closed or that it was unnecessary. As a result, the new regime found Bektashism harmful to civilization and closed the sect and after the freedom environment of the Constitutional Monarchy years, recognition efforts of Bektashis ended in disappointment once again. This article tries to analyse this process by using the mentioned sources and to evaluate the approach of the Republican administration to the sects and the Bektashi sect in particular, in its historical depth, by concentrating on the years 1921-1931.